Loss of Klotho Contributes to Kidney Injury by Derepression of Wnt/β-Catenin Signaling - Zhou, Lili; Li, Yingjian; Zhou, Dong; Tan, Roderick J.; Liu, Youhua (Journal of the American Society of Nephrology, 2013)
Aging is an independent risk factor for CKD, but the molecular mechanisms that link aging and CKD are not well understood. The antiaging protein Klotho may be an endogenous antagonist of Wnt/β-catenin signaling, which promotes fibrogenesis, suggesting that loss of Klotho may contribute to CKD through increased Wnt/β-catenin activity. Here, normal adult kidneys highly expressed Klotho in the tubular epithelium, but various models of nephropathy exhibited markedly less expression of Klotho. Loss of Klotho was closely associated with increased β-catenin in the diseased kidneys, suggesting an inverse correlation between Klotho and canonical Wnt signaling. In vitro, both full-length and secreted Klotho bound to multiple Wnts, including Wnt1, Wnt4, and Wnt7a. Klotho repressed gene transcription induced by Wnt but not by active β-catenin. Furthermore, Klotho blocked Wnt-triggered activation and nuclear translocation of β-catenin, as well as the expression of its target genes in tubular epithelial cells. Investigating potential mediators of Klotho loss in CKD, we found that TGF-β1 suppressed Klotho expression and concomitantly activated β-catenin; conversely, overexpression of Klotho abolished fibrogenic effects of TGF-β1. In two mouse models of CKD induced by unilateral ureteral obstruction or adriamycin, in vivo expression of secreted Klotho inhibited the activation of renal β-catenin and expression of its target genes. Secreted Klotho also suppressed myofibroblast activation, reduced matrix expression, and ameliorated renal fibrosis. Taken together, these results suggest that Klotho is an antagonist of endogenous Wnt/β-catenin activity; therefore, loss of Klotho may contribute to kidney injury by releasing the repression of pathogenic Wnt/β-catenin signaling.